Percepção de uma comunidade acadêmica sobre a Homeopatia no ambiente de trabalho - Cecília Beber de Souza; Solange Cervinho Bicalho Godoy. (2022)
Introduction: The World Health Organization advocates the use of Integrative and Complementary Practices in Health (PICS). Through the Ministry of Health, Brazil has been incorporating, in recent years, several practical health modalities, within the scope of the Unified Health System. Homeopathy was one of the first modalities to be implemented, through Ordinance 91 of the Ministry of Health, in 2006. of integrality. They emphasize a holistic and well-stratified approach to health – sometimes being functional, they treat social people as a whole and not just their individual condition. They are characterized as cost-effective technologies with great potential to bring improvements to people's quality of life, thus favoring workers' QOL. Objective: To analyze the perceptions of FAO/UFMG workers about homeopathy, as an integrative and complementary practice. Method: This is a study with a qualitative approach and descriptive purpose of the case study type. The technique used to collect information was a semi-structured interview. The interview script for the workers included questions based on initial questions based on hypotheses and theories relevant to the research, accompanied by a section for recording socioeconomic, demographic and work-related data. Data analysis was performed using the content analysis technique (BARDIN, 2016). Results and Conclusion: The results were described in three categories for better analysis and understanding of the data obtained, where it was concluded that the offer of Homeopathy services was well accepted by the sample of respondents that represented the academic community of FAO/UFMG. In this way, the insertion of Homeopathy within the academic community of FAO/UFMG proposes to take care of the integral being, in a positive perspective of health, developing a practice of health promotion. The great value attributed to homeopathy concerns the fact that it practice favoring humanization and integrality, being then characterized as a practice that promotes humanization. The implementation of this service at FAO/UFMG will allow the public during the homeopathic consultation a dialogic reception that would be a conversation technique based on some ethical-cognitive dispositions, among which the recognition of the other as a legitimate other. This opening to a conversation that will not be guided by positivist objectivity in the search for symptoms of the disease, but towards a practice focused on integrality.